1999
DOI: 10.4141/s97-096
|View full text |Cite
|
Sign up to set email alerts
|

Tillage effects on the dynamics of total and corn-residue-derived soil organic matter in two southern Ontario soils

Abstract: . 1999. Tillage effects on the dynamics of total and corn-residue-derived soil organic matter in two southern Ontario soils. Can. J. Soil Sci. 79: 473-480. Agricultural management practices affect the dynamics of soil organic matter (SOM) by influencing the amount of plant residues returned to the soil and rate of residue and SOM decomposition. Total organic C and δ 13 C of soil were measured in two field experiments involving corn cropping to determine the effect of tillage practices on SOM dynamics. Minimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 30 publications
6
39
1
Order By: Relevance
“…Studies have shown that manure application increased SOC and nutrient status in the soil (Webster and Goulding, 1989;Collins et al, 1992;Rochett e and Gregorich, 1998) and labile carbon pools (Aoyama et al, 1999;Mikha and Rice, 2004). Total corn rootderived C (C in root biomass plus that in rhizodeposition) contributes from 1.5 times to more than 3 times more C to SOC than shoot-derived C (Balesdent and Balabane, 1996;Wanniarachchi et al, 1999;Wilts et al, 2004;Hooker et al, 2005). Hooker et al (2005) att ributed the diff erence to dissimilar C cycling rates of shoot and root material.…”
Section: Biomass and Bioenergy Concernsmentioning
confidence: 99%
“…Studies have shown that manure application increased SOC and nutrient status in the soil (Webster and Goulding, 1989;Collins et al, 1992;Rochett e and Gregorich, 1998) and labile carbon pools (Aoyama et al, 1999;Mikha and Rice, 2004). Total corn rootderived C (C in root biomass plus that in rhizodeposition) contributes from 1.5 times to more than 3 times more C to SOC than shoot-derived C (Balesdent and Balabane, 1996;Wanniarachchi et al, 1999;Wilts et al, 2004;Hooker et al, 2005). Hooker et al (2005) att ributed the diff erence to dissimilar C cycling rates of shoot and root material.…”
Section: Biomass and Bioenergy Concernsmentioning
confidence: 99%
“…However, soil erosion and redistribution over a prolonged period can also affect SOC storage under NT. VandenBygaart et al (2002) concluded that soils that had lost SOC through soil erosion had a high potential to gain SOC when converted Campbell et al (1996a) (1), Campbell et al (1996b) (2), Campbell et al (1995a) (3), Larney et al (1997) (4), Nyborg, et al (1995) (5), Campbell et al (2001a) (6), Grant and Lafond (1994) (7), McConkey et al (2003) (8), Hao et al (2001) (9), Elliott and Efetha (1999) (10), Doormar and Carefoot (1998) (11), Franzluebbers and Arshad (1996) (12), Carter (1996) (13), Yang and Kay, (2001a) (14), Wanniarachchi et al, (1999) (15), VandenBygaart et al (2002) (16), Carter et al (2002) (17), Carter and Sanderson 2001 (18), Angers, et al (1997) (19), Carter and Kunelius 1986 (20), Angers et al 1995 (21), Winter et al 1990 (22), Yang and Kay (2001b) (23).…”
Section: Tillage Management and C Storagementioning
confidence: 99%
“…Outliers removed from Yang and Kay (2001b). Data from Carter and Kunelius (1986), Winter et al (1990), Angers et al (1993aAngers et al ( , 1995Angers et al ( , 1997, Grant and Lafond (1994), Campbell et al (1995aCampbell et al ( , 1996aCampbell et al ( , b, 2001a, Nyborg et al (1995), Carter (1996, Franzluebbers and Arshad (1996), Larney et al (1997), Carefoot (1998), Miller et al (1999), Wanniarachchi et al (1999) achieved, although at low rates, in wheat-fallow systems converted to NT in cool, semi-arid climates such as those in the Canadian Prairies (Table 4).…”
Section: Tillage Management and C Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, distribution of SOM within the plow layer is influenced by tillage practice. For example, Wanniarachchi et al (1999) found that minimum tillage and NT increased corn-derived C in the surface layer (0-5 cm) over that with CT. Similar results have been reported by Angers et al (1995), McCarty et al (1998) and Yang and Wander (1999).…”
mentioning
confidence: 99%